Toll-like receptor expression and functional behavior in platelets from patients with systemic lupus erythematosus - Baroni Pietto, Maria Constanza (2024)
Background: Multiple blood cell abnormalities participate in the development of inflammation in systemic lupus erythematosus (SLE). Although platelets have been suggested as one of these contributors through the release of their content during activation, there are limited specific data about their role as immune players in SLE. Materials and Methods: Thirteen SLE patients were included. Flow cytometry was used to measure Toll-like receptors (TLR) 2, 4, and 9 in resting platelets, platelet-activation markers (PAC-1 binding, P-selectin, CD63, and CD40 ligand -L) and platelet-leukocyte aggregates before and after specific TLR stimulation. Soluble CD40L and von Willebrand factor (vWf) release from stimulated platelets was measured using ELISA. Results: In resting conditions, SLE platelets showed normal expression levels of TLR 2, 4 and 9. Platelet surface activation markers, soluble CD40L, and vWf release were normal at baseline and after TLR stimulation. Plateletmonocyte aggregates were elevated in resting conditions in SLE samples and showed only a marginal increase after TLR stimulation, while baseline and stimulated platelet-neutrophil and platelet-lymphocyte aggregates were normal. C-reactive protein levels positively correlated with platelet-monocyte aggregates both at baseline and after stimulation with the TLR-2 agonist PAM3CSK4, suggesting these complexes could reflect the inflammatory activity in SLE. In our cohort, 12 of 13 patients received treatment with hydroxychloroquine (HCQ), a known inhibitor of endosomal activity and a potential inhibitor of platelet activation. The fact that SLE platelets showed an adequate response to TLR agonists suggests that, despite this treatment, they retain the ability to respond to the increased levels of damage-associated molecular patterns (DAMPs), which represent known TLR ligands, present in the circulation of SLE patients. Interestingly, elevated plasma levels of high mobility group box 1 (HMGB1), a classical DAMP, correlated with vWf release from TLR-stimulated platelets, suggesting that HMGB1 may also be released by platelets, thereby creating a positive feedback loop for platelet activation that contributes to inflammation. Conclusion: Our study demonstrates normal platelet TLR expression and function together with increased circulating platelet-monocyte aggregates. In addition, a direct correlation was observed between plasma HMGB1 levels and platelet vWf release following TLR2 stimulation. This platelet behavior in a group of patients undergoing HCQ treatment suggests that platelets could play a role in the inflammatory state of SLE.